The influence of minimalist, maximalist and conventional footwear on impact shock attenuation during running - Sinclair, J. (Movement & Sport Sciences - Science & Motricité, 2017)
The current investigation examined the effects of minimalist, maximalist and conventional footwear on skeletal accelerations and shock attenuation during running. Ten male runners ran at 4.0 m.s-1 in minimalist, maximalist and conventional footwear. Axial accelerations were measured using accelerometers positioned at the tibia and sacrum. Peak tibial and sacral accelerations were obtained and used to calculate the extent of shock attenuation. The results showed that peak tibial acceleration and shock attenuation were significantly lower in the minimalist in comparison to the conventional and maximalist footwear. Running in conventional and maximalist footwear may place increased demands on the musculoskeletal structures in order to attenuate impact transients, which may be detrimental to passive tissues.